Experimental evaluation of radioiodinated sennoside B as a necrosis-avid tracer agent. (February 2015) - Zhang, Dongjian; Huang, Dejian; Ji, Yun; Jiang, Cuihua; Li, Yue; Gao, Meng; Yao, Nan; Liu, Xuejiao; Shao, Haibo; Jing, Su; Ni, Yicheng; Yin, Zhiqi; et al.
Abstract Necrosis-avid agents are a class of compounds that selectively accumulate in the necrotic tissues after systemic administration, which can be used for in vivo necrosis imaging and targeted therapies. In order to search for a necrosis-avid tracer agent with improved drugability, we labelled iodine-131 on sennoside B (SB) as a naturally occurring median dianthrone compound. The necrosis targetability and clearance properties of 131I-SB were evaluated in model rats with liver and muscle necrosis. On SPECT/CT images, a "hot spot" in the infarcted liver lobe and necrotic muscle was persistently observed at 24 h and 72 h post-injection (p.i.). Gamma counting of the tissues of interest revealed a radioactivity ratio of necrotic to viable liver at 4.6 and 3.4 and of necrotic to viable muscle at 7.0 and 8.8 at 24 h and 72 h p.i., respectively. The good match of autoradiographs and fluoromicroscopic images with corresponding histochemical staining suggested preferential uptake of 131I-SB in necrotic tissue. Pharmacokinetic study revealed that 131I-SB has an elimination half-life of 8.6 h. This study indicates that 131I-SB shows not only prominent necrosis avidity but also favourable pharmacokinetics, which may serve as a potential necrosis-avid diagnostic agent for assessment of tissue viability.